Specific association between an endoribonucleolytic sequence from a satellite RNA and a substrate analogue containing a 2'-5' phosphodiester. - Feldstein, P A (1990)
Both polarities of the satellite RNA of tobacco ringspot virus are sources of self-cleaving sequences. RNA of the less abundant, negative polarity, designated sTobRV-(-)RNA, has cleaving activity that was mapped previously to two noncontiguous regions of the polyribonucleotide chain. Endoribonucleolytic oligoribonucleotides (E) corresponding to the larger of the two regions cleaved smaller substrate oligoribonucleotides, at the ApG phosphodiester that is cleaved in sTobRV(-)RNA. An analogue of the substrate, which has a 2'-5' ApG phosphodiester, was not cleaved by E but acted as a competitive inhibitor of the cleavage of substrate. The analogue served as a primer, and E served as template, for reverse transcriptase-catalyzed copying of specific E sequences. The sequences transcribed suggest base pairing between the 5' region of E and a portion of the substrate that is located 3' to, but does not include, the ApG phosphodiester. Results from other experiments indicate this base pairing is a part of the functional cleavage complex. The association of the ends of E and substrate anticipates a second, 4-base-pair association between E and a portion of substrate that is 5' to, but does not include, the ApG phosphodiester. The effects of compensating mutations in E and substrate oligoribonucleotides support the existence of this second association in the active cleavage complex.